KEPEMIMPINAN BADAN KOORDINASI KEGIATAN KESEJAHTERAAN SOSIAL VERSUS KONSEP WEWENANG MAX WEBER - SUGIYANTO SUGIYANTO; ANALIUS GIAWA; MUSOLI MUSOLI (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2020)
Abstrak. The coordinating body of social welfare activities (BK3S), a non-governmental organization that has the task and responsibility of coordinating the implementation of social welfare efforts organized by social welfare institutions (LKS) for the community, especially gives services to people with social welfare problems. BK3S DIY social actions as government partners cq the social office has the authority to regulate, provide recommendations for licensing, advocate for organizations and strengthen the existence of LKS. The practice of organizing, coordinating, advocating and strengthening organizational governance is analyzed through Max Weber's authority theory. The results of the analysis of social actions in the practice of regulating, coordinating, advocating and engaging in strengthening institutions with Max Weber's theory of authority obtained organizational identity so that it looks strangely different from BK3S or other social organizations. Abstrak. Badan Koordinasi Kegiatan Kesejahteraan Sosial (BK3S) adalah lembaga non pemerintah. Tugas dan tanggungjawabnya adalah melakukan koordinasi penyelenggaraan berbagai usaha kesejahteraan sosial oleh Lembaga Kesejahteraan Sosial (LKS) untuk masyarakat terutama memberi pelayanan kepada penyandang masalah kesejahteraan sosial. Tindakan sosial BK3S DIY sebagai mitra pemerintah cq dinas sosial mempunyai kewenangan mengatur, memberi rekomendasi perizinan, mengadvokasi organisasi dan memperkuat keberadaan LKS. Praktik mengatur, mengoordinasikan, mengadvokasi dan memperkuat tata kelola organisasi ini dianalisis melalui teori kewenangan Max Weber. Hasil analisis tindakan sosial dalam praktik pengaturan, koordinasi, advokasi dan keterlibatan memperkuat kelembagaan dengan teori kewenangan Max Weber diperoleh identitas organisasi sehingga tampak kekhasan dan pembeda dengan BK3S atau organisasi sosial lainnya.